2014
DOI: 10.1186/bf03352188
|View full text |Cite
|
Sign up to set email alerts
|

MOISE: A pilot experiment towards long term sea-floor geophysical observatories

Abstract: We describe the scientific purposes and experimental set-up of an international deployment of a 3 component broadband seismometer package on the ocean floor in Monterey Bay which took place during the summer of 1997. Highlights of this experiment were the installation, performed using a remotely operated vehicle (ROV), the underwater connection of the different components of the package, and the successful retrieval of 3 months of broadband seismic and auxiliary data. Examples of recordings of teleseisms and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 15 publications
0
22
1
1
Order By: Relevance
“…In particular, sensors can be deployed at the seafloor; they can be partially or completely buried in the sediment layer (Romanowicz et al, 1998;Collins et al, 2001;Stephen et al, 2003;Shinohara et al, 2006;Duennebier and Sutton, 2007) or ▴ Figure 2. Dominant sources of signal in the seismic spectrum are indicated in their corresponding frequency bands, spanning from infragravity waves > 25 s (< 0:04 Hz) to local seismicity 0.05-0.25 s (4-20 Hz).…”
Section: Sensor Type and Installation Proceduresmentioning
confidence: 99%
“…In particular, sensors can be deployed at the seafloor; they can be partially or completely buried in the sediment layer (Romanowicz et al, 1998;Collins et al, 2001;Stephen et al, 2003;Shinohara et al, 2006;Duennebier and Sutton, 2007) or ▴ Figure 2. Dominant sources of signal in the seismic spectrum are indicated in their corresponding frequency bands, spanning from infragravity waves > 25 s (< 0:04 Hz) to local seismicity 0.05-0.25 s (4-20 Hz).…”
Section: Sensor Type and Installation Proceduresmentioning
confidence: 99%
“…Previous experiments [e.g., Sutton et al, 1981;Duennebier and Sutton, 1995] showed that it is important to minimize water flow around the seismometer. To prevent noise from water circulation within the caisson, and similarly to the previous temporary MOISE experiment [Romanowicz et al, 1998], tiny glass beads (0.8 mm diameter) were poured into the PVC caisson to completely cover the pressure vessel. The seismometer package is now buried at least 10 cm beneath the seafloor.…”
Section: Instrument Testing and Deploymentmentioning
confidence: 99%
“…The MOBB is a continuously operated broadband seismic station and is considered the first step toward extending the Berkeley Digital Seismic Network (BDSN) westward of the Pacific‐North America plate boundary. It follows from the experience gained previously during the 3‐monthlong MOISE deployment in 1997, which was located about 10 km to the west [ Romanowicz et al , 1998; Stutzmann et al , 2001].…”
Section: Introductionmentioning
confidence: 99%